Final environmental impact statement for the wilderness recommendations : Glacier Bay National Park and Preserve, Alaska. - United States. National Park Service. Alaska Regional Office. (Anchorage, Alaska : Alaska Regional Office, National Park Service, 1988)
"September 1988"--P. [3] of cover. Shipping list no.: 88-676-P. Cover title: Final environmental impact statement, wilderness recommendation: Glacier Bay National Park and Preserve/Alaska. "NPS D-26A"--P. [3] of cover. Includes index. Bibliography: p. 421-426. Mode of access: Internet.